Dampak Aktivitas Pertambangan Nikel terhadap Kehidupan Keagamaan Masyarakat Kabaena Barat Kabupaten Bombana - Muhammad Al Fatur; Madi Madi; Abdul Rahim (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the impact of nickel mining activities on the religious life of the community in West Kabaena District, Bombana Regency. The research employed a qualitative method with a descriptive approach to obtain an in-depth understanding of the social and religious changes occurring within the community. Data were collected through interviews, observations, and documentation involving religious leaders, community leaders, youth representatives, and mining workers. The collected data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that nickel mining activities have not diminished the community’s understanding of environmental stewardship as a religious responsibility. However, increasing economic dependence on the mining sector has gradually reduced public concern for environmental preservation. In the religious sphere, mining activities have contributed positively by supporting the construction and improvement of worship facilities and religious programs. Nevertheless, work-related demands have reduced the participation of some community members in religious activities. Furthermore, mining activities have affected social solidarity within the community. Values such as brotherhood, mutual cooperation, and social care remain preserved, although changes in social interaction patterns and widening economic disparities have become increasingly apparent. The study concludes that nickel mining activities generate both positive and negative impacts on the religious life of the West Kabaena community. Therefore, balanced policies integrating economic development, environmental sustainability, and religious values are essential to promote sustainable community welfare and strengthen social harmony.